Effect of prior cold work on age hardening of Cu-4Ti-1Cd alloy - Markandeya R.; Nagarjuna S.; Sarma D.S. (My University, 2025)
This research is part of a project whose scope was to develop high strength ternary alloys based on Cu-Ti system with the primary aim of substituting them for toxic and expensive Cu-Be alloys. In this pursuit, age hardening behaviour of Cu-4Ti-1Cd alloy has already been investigated and the present paper reports the investigations on the influence of prior cold work by rolling of 50, 75 and 90% on the age hardening of a Cu-4Ti-1Cd alloy using hardness and tensile tests and optical as well as transmission electron microscopy. As a result of cold work followed by aging, hardness of the alloy increased from 237 Hv in solution treated condition to 425 Hv on 90% cold work and peak aging. Similarly, yield and tensile strengths of the alloy reached maxima of 1037 and 1252 MPa respectively on 90% deformation and peak aging. The microstructure of the deformed alloy exhibited elongated grains and deformation bands. The maximum strength on peak aging was obtained due to precipitation of ordered, metastable and coherent βl, Cu4Ti phase in addition to high dislocation density and deformation twins. Both hardness and strength of the alloy decreased on overaging due to the formation of incoherent and equilibrium β, Cu3Ti phase. However, the morphology of the discontinuous precipitation was changed to globular shape due to large deformations and overaging. © 2006 Springer Science + Business Media, Inc.